ANALYSIS OF JOB PROMOTION AND WORK ENVIRONMENT ON PERFORMANCE TEACHERS THROUGH MOTIVATION AT SMA NEGERI 1 BANDAR BENER MERIAH REGENCY - Rukaiyah; Kiki Farida Ferine; Elfitra Desy Surya (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the influence of job promotion and work environment on teacher performance with motivation as an intervening variable at SMA Negeri 1 Bandar, Bener Meriah Regency. A quantitative approach was used with a survey method through the distribution of questionnaires to teachers as respondents. The job promotion variable was measured based on experience, work performance, and career opportunities, while the work environment included aspects of cleanliness, tidiness, and comfort. Motivation was analyzed as a psychological factor that encourages teachers to work optimally. Data were analyzed using path analysis techniques to examine the direct and indirect effects between variables. The results showed that job promotion and work environment had a positive and significant effect on teacher performance, both directly and through motivation. These findings imply that schools need to develop fair promotion policies and create a conducive work environment to improve teacher motivation and performance.